Challenges in psychotherapy: Complex trauma, attachment and dissociation - Morales Aguilar, Diana Patricia (2018)
In the 21st century, the Psychotherapy continues to take giant steps with a comprehensive perspective. The areas of the current challenges of Psychotherapy are numerous, this article presents only one of them, the study of the relationship between Complex Trauma, Attachment and Dissociation. Many international colleagues such as Van der Hart O, Nijenhuis E, Steele K., Van der Kolk B., Pelcovitz D., Roth S., Mandel F., McFarlane A., Herman, J., inter alia , have given a great scientific contribution that helps us to generate a better dimensional and categorical diagnosis following the new indications of the DSMV, but more important , they indicate that the way to solve a problem that a patient brings us is not only one, it means there is a greater demand for those who work in the clinical area and especially in Psychotherapy, an update and constant study of new intervention approaches.